A Sample-to-Sequence Protocol for Genus Targeted Transcriptomic Profiling: Application to Marine Synechococcus - Pitt, Frances D.; Millard, Andrew; Ostrowski, Martin; Dervish, Suat; Mazard, Sophie; Paulsen, Ian T.; Zubkov, Mikhail V.; Scanlan, David J. (Frontiers in Microbiology, 2016)
Recent studies using whole community metagenomic and metatranscriptomic approaches are revealing important new insights into the functional potential and activity of natural marine microbial communities. Here, we complement these approaches by describing a complete ocean sample-to-sequence protocol, specifically designed to target a single bacterial genus for purposes of both DNA and RNA profiling using fluorescence activated cell sorting. The importance of defining and understanding the effects of a sampling protocol are critical if we are to gain meaningful data from environmental surveys. Rigorous pipeline trials with a cultured isolate, Synechococcus sp. BL107 demonstrate that water filtration has a well-defined but limited impact on the transcriptomic profile of this organism, whilst sample storage and multiple rounds of cell sorting have almost no effect on the resulting RNA sequence profile. Attractively, the means to replicate the sampling strategy is within the budget and expertise of most researchers.